Gene Expression and Proteomics Studies Suggest an Involvement of Multiple Pathways Under Day and Day–Night Combined Heat Stresses During Grain Filling in Wheat - Chunduri, Venkatesh; Kaur, Amandeep; Kaur, Shubhpreet; Kumar, Aman; Sharma, Saloni; Sharma, Natasha; Singh, Pargat; Kapoor, Payal; Kaur, Satveer; Kumari, Anita; Roy, Joy; Kaur, Jaspreet; et al. (Frontiers in Plant Science, 2021)
Recent weather fluctuations during grain filling period are associated with the reduction in wheat grain yield and quality in India. Field studies on heat stress are complicated by confounders. In this study, we tried to find out the effect of day and day-night combined heat stresses and reason behind, through gene and protein expression studies. Expression studies for genes related to multiple pathways that included starch biosynthesis pathway, starch transporters, transcription factors, stress-responsive and storage proteins, at four grain developmental stages indicated the involvement of multiple pathways. Under control conditions, their expression was observed till 28 days after anthesis (DAA). However, their expression was observed till 14 DAA under day-stress and 7 DAA under day-night stress. Protein profiles generated using 2D-PAGE and MALDI-TOF MS/MS showed differential expression of proteins belonging to multiple pathways that included up-regulation of proteins related to translation and selected seed storage proteins (gliadins and low molecular weight glutenin) and down-regulation of proteins related to glycolysis, photosynthesis, defence and selected seed storage proteins (high molecular weight glutenins). Overall, defence response in day heat stress caused early gene expression and day-night heat stress caused suppression of gene expression by activating multiple path-ways which ultimately lead to a reduction in grain filling duration, yield, grain weight and processing quality.